(untitled) (Research, Society and Development, 2022)
Objective: To map the strategies for preventing and coping with sensory crises in autistic adolescents. Method: This is a scope review protocol, based on the Joanna Briggs Institute manual and Preferred Reporting Items for Systematic Reviews and Meta-Analyses - Extension for Scoping Reviews. The protocol was registered in the Open Science Framework Platform, nº osf.io/fxnh4. The Descriptors in Health Sciences and Medical Subject Headings were chosen: related to the terms Adolescent, Autistic Spectrum Disorder and Sensory Crises, to proceed with the search equation in the Lilacs and SciELO databases, via the Virtual Health Library, Medline, via PubMed, and Scopus. The inclusion criteria established are articles in Portuguese, English and Spanish, with no time frame, and that answer the guiding question: What are the strategies for preventing and coping with sensory crises in autistic adolescents?. Two reviewers will screen titles and abstracts, as well as extract data independently. The results will be classified into conceptual analysis categories based on thematic categorical analysis, based on Bardin’s content analysis.